Sustainable Economic Development : Concept, Principles and Management from Islamic Perspective - Ibrahim, Patmawati; Ab Rahman, Asmak; Basir, Siti Arni (2010)
The basic concern of development in Islamic economic system is on human welfare. This is in line with the very basic objective of Islamic jurisprudence (Shari’ah ) which puts important to the welfare of the people and their relief from hardship. Economic development should be consistent with this central objective of shari`ah. The center for development process in Islam relies on man as an economic agent. It is man to be educated on the entire development process by integrating sosial development, economic development and environmental conservation and protection. This paper attempts to explain the concept, principles and management of sustainable economic development from Islamic perspective. The paper would start by defining the concept of sustainable economic development and developmentgoals. Next, the Islamic principles for sustainable economic development would be discussed, followed by the discussion on the management of sustainable economic development from Islamic perspective. In conclusion, the paper strongly suggests the economic development process to fully adhere to the Islamic principles as the key for sustainable development which covers both the material and non-material aspects of life.